Anisotropic structure of the African upper mantle from Rayleigh and Love wave tomography - (:unkn) unknown (My University, 2006)
The geodynamics of the mantle below Africa is not well understood and anisotropy tomography can provide new insight into the coupling between the African plate and the underlying mantle convection. In order to study the anisotropic structure of the upper mantle beneath Africa, we have measured phase velocities of 2900 Rayleigh and 1050 Love waves using the roller-coaster algorithm [Beucler, E., Stutzmann, E., Montagner, J.-P., 2003. Surface-wave higher mode phase velocity measurments, using a roller-coaster type algorithm. Geophys. J. Int. 155 (1), 289–307]. These phase velocities have been inverted to obtain a new tomographic model that gives access to isotropic SV-wave velocity perturbations, azimuthal and radial anisotropies. Isotropic SV-wave velocity maps have a lateral resolution of 500 km. Anisotropy parameters have a lateral resolution of 1000 km which is uniform over Africa for azimuthal anisotropy but decreases at the West and South of Africa for radial anisotropy. At shallow depth, azimuthal anisotropy varies over horizontal distances much smaller than the continent scale. At 280 km depth, azimuthal anisotropy is roughly N-S, except in the Afar area, which might indicate differential motion between the African plate and the underlying mantle. The three cratons of West Africa, Congo and Kalahari are associated with fast velocities and transverse anisotropy that decrease very gradually down to 300 km depth. On the other hand, we observe a significant change in the direction and amplitude of azimuthal anisotropy at about 180 km depth, which could be the signature of the root of these cratons. The Tanzania craton is a shallower structure than the other African cratons and the slow velocities (−2%) observed on the maps at 180 and 280 km depth could be the signature of hot material such as a plume head below the craton. This slow velocity anomaly extends toward the Afar and azimuthal anisotropy fast directions are N-S at 180 km depth, indicati
Keywords: African Research